Molecular Characterization of Putative Virulence Determinants in Burkholderia pseudomallei - Suat Moi Puah; S. D. Puthucheary; Jin Town Wang; Yi Jiun Pan; Kek Heng Chua (The Scientific World Journal)
The Gram-negative saprophyte Burkholderia pseudomallei is the causative agent of melioidosis, an infectious disease which is endemic in Southeast Asia and northern Australia. This bacterium possesses many virulence factors which are thought to contribute to its survival and pathogenicity. Using a virulent clinical isolate of B. pseudomallei and an attenuated strain of the same B. pseudomallei isolate, 6 genes BPSL2033, BP1026B_I2784, BP1026B_I2780, BURPS1106A_A0094, BURPS1106A_1131, and BURPS1710A_1419 were identified earlier by PCR-based subtractive hybridization. These genes were extensively characterized at the molecular level, together with an additional gene BPSL3147 that had been identified by other investigators. Through a reverse genetic approach, single-gene knockout mutants were successfully constructed by using site-specific insertion mutagenesis and were confirmed by PCR. BPSL2033::Km and BURPS1710A_1419::Km mutants showed reduced rates of survival inside macrophage RAW 264.7 cells and also low levels of virulence in the nematode infection model. BPSL2033::Km demonstrated weak statistical significance (P=0.049) at 8 hours after infection in macrophage infection study but this was not seen in BURPS1710A_1419::Km. Nevertheless, complemented strains of both genes were able to partially restore the gene defects in both in vitro and in vivo studies, thus suggesting that they individually play a minor role in the virulence of B. pseudomallei.